Sugar and micronutrient intake within elite youth British soccer players: The nutritional transition from schoolboy to fulltime soccer player - Naughton, R.; Drust, B.; O'Boyle, A.; Morgans, R.; Abayomi, J.; Davies, I. G.; Morton, J. P.; Mahon, E. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction It is recommended that soccer players consume a diet high in carbohydrate to augment performance. However, growing evidence suggests there is a link between high free-sugar intake (>5% total energy intake (TEI)) and some metabolic diseases (1). Additionally, recent data has found that soccer players are at risk of oral caries, which was linked to free-sugar intake (2). Little is currently known about the free-sugar intake within elite British youth soccer players and, consequently, their risk to adverse health conditions. We therefore tested the hypothesis that elite British youth soccer players consumed above the current UK DRV (5% TEI) for free-sugars. Method: Players from an English Premier League academy under (U) 18 (n = 13); U15/16 (n = 25); U13/14 (n = 21)] completed a 7-day food diary over a training period in which no competitive games took place. Upon analysis, using dietary analysis software (Nutritics Ltd, Ireland), these data were compared to the current UK DRV for free-sugar via a t-test. Intakes between squads was analysed using a one-way ANOVA. All data are expressed as means (SD), statistical significance p < 0.05. Results The U13/14s (TEI, 10.0 17.7%) and U15/16s (TEI, 11.2 30.0%) both consumed higher amounts of free-sugar in comparison to the UK DRV of TEI 5% (P < 0.01), conversely, the U18s (TEI, 5.1 12.7%) were no different from the DRV. Furthermore, the free-sugar intake of the U18s was significantly lower than that of the U13/14s and U15/16s (P < 0.01). Discussion: Our data provides novel evidence on the free-sugar intake across a range of ages within an elite youth British soccer academy. It would appear that there is a shift in nutritional habits from when a player transitions to fulltime (U18s) from schoolboy (U13-U16s). However, it may be put forward that as the tested population are athletes they may have need for a higher carbohydrate intake in comparison to the UK DRV, which may lead to higher free-sugar intake than the general population. Further research is needed to establish if there is any health risk to this population as a result of an increased free-sugar intake (>5% TEI).